A cross-sectional study investigating the L-shaped relationship between urinary albumin creatinine ratio and overweight/obesity in children and adolescents - Cui, Zhengjiu; Chen, Xiaorui; Zhai, Siming; Luo, Fei; Wang, Yuanyuan; Hu, Chanchan; Yuan, Bin (Scientific reports, 2025)
Childhood and adolescent obesity has become one of the most serious public health problems worldwide, and obesity may have potential effects on kidney health. The urinary albumin creatinine ratio (UACR) is a sensitive indicator for assessing renal impairment. Relevant studies on pediatric and adolescent populations are more limited and controversial. This study aimed to clarify the relationship between UACR and overweight/obesity in children and adolescents in the United States, thereby providing new insights and recommendations for the clinical management and prevention of kidney disease. This study utilized data from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2016. Variables were derived from demographic, examination, and laboratory data. Overweight/obesity status was assessed using BMI criteria, and random urine samples were used to measure UACR. The association between UACR and overweight/obesity was assessed using descriptive statistics, multivariate logistic regression analysis, subgroup analysis, and curve-fitting analysis. In this study of 4116 participants aged 8–19, multivariate logistic regression analysis revealed a significant negative association between UACR and overweight/obesity (OR = 0.32; 95% CI 0.26–0.38; P < 0.001). The interaction P-values were all greater than 0.05 in the interaction of subgroups, indicating that the findings were very stable and consistent between subgroups. In addition, smoothed curve fitting and threshold effect analyses revealed a nonlinear relationship between UACR and overweight/obesity, with an inflection point for log(UACR) determined to be 1.435 mg/g. The findings suggest a significant nonlinear negative correlation between UACR and overweight/obesity in the pediatric and adolescent populations. Until a precise mechanism of association is found, maintaining a standard range of BMI in all age groups may reduce the incidence of albuminuria in this population.